Respuesta :
Answer: The answers are given below.
Step-by-step explanation: We are given to factorise some quadratic expressions.
We will be using the following factorisation formula:
[tex]x^2+ax+bx+ab=(x+a)(x+b).[/tex]
The factorisation is as follows:
We have
[tex](1)~3ab-5ax+9b-15x\\\\=a(3b-5x)+3(3b-5x)\\\\=(3b-5x)(a+3).[/tex]
Thus, option (B) [tex](3b-5x)(a+3)[/tex] is correct.
[tex](2)~5x(x+3)+6(x+3)\\\\=(x+3)(5x+6).[/tex]
Thus, option (B) [tex](x+3)(5x+6)[/tex] is correct.
[tex](3)~2cb+7cx+2b+7x\\\\=c(2b+7x)+1(2b+7x)\\\\=(2b+7x)(c+1).[/tex]
Thus, option (B) [tex](2b+7x)(c+1)[/tex] is correct
[tex](4)~21x^3+35x^2+9x+15\\\\=7x^2(3x+5)+3(3x+5)\\\\=(3x+5)(7x^2+3).[/tex]
Thus, option (D) [tex](3x+5)(7x^2+3)[/tex] is correct.
[tex](5)~9xy+36x-10y-40\\\\=9x(y+4)-10(y+4)=(y+4)(9x-10).[/tex]
Thus, option (C) [tex](y+4)(9x-10)[/tex] is the correct option.
[tex](6)~14bx^2-7x^3-4b+2x\\\\=7x^2(2b-x)-2(2b-x)\\\\=(2b-x)(7x^2-2).[/tex]
Thus, option (B) [tex](2b-x)(7x^2-2)[/tex] is the correct option.
[tex](7)~4xy+9x+24y+54\\\\=x(4y+9)+6(4y+9)\\\\=(4y+9)(x+6).[/tex]
Thus, option (D) [tex](4y+9)(x+6)[/tex] is correct.
Answer:
The correct Answer is D. (4y + 9)(x + 6)
Step-by-step explanation:
took thee Test